Roady: The Application for Assessing Risk Factors in Driving Activities - Krajangiam, Chotima; Thianniwet, Thammasak (Journal of Applied Informatics and Technology, 2025)
Road traffic accidents are a major global cause of mortality. Factors contributing to accidents include exceeding the speed limit, environmental conditions, and vehicle issues. Thailand has the second-highest fatality rate in Asia. The top three causes of accidents in Thailand are driving faster than the legal limit, dangerous lane changes, and driving too close to the vehicle ahead. One way to encourage safe driving is to identify risk factors. In this work, we: (1) propose a framework and develop a mobile application (Roady) to assess risk factors for driving over speed limits, and (2) develop a design prototype that incorporates gamification principles to encourage and motivate users toward safe driving practices. This application was evaluated on a university campus. The evaluation of driving behavior detection regarding overspeeding showed an accuracy of 87.7%. We deployed the Roady application to the App Store and tested it with 53 users. The usability test showed the highest usability level of 4.53 (\bar{x}). We then evaluated our gamification design prototype. The results showed mean scores as high as 4.57 (\bar{x}). While various technologies are available today to assist in risk detection, we believe that using mobile phones—which are widely used—to identify driving hazards can encourage safe driving and reduce the number of traffic accidents.